Public Policies in Reducing Informality and Poverty, Costa Rica, Central Region, 2018-2024 - Suárez Espinoza, Kerlyn (2026)
This article analyzes, from the perspective neo-institutional and territorial economy, through a qualitative-descriptive method, using secondary and primary sources such as INEC, Ministry of Labor, ILO, as well as opinion survey conducted with informal workers and experts on the effectiveness of public policy implementation in reducing informality and poverty in the Central Region of Costa Rica during the period 2018-2024. This is crucial, since informal workers are trapped in a cycle of low wages and lack of access to basic rights and essential services including housing, healthcare and education, while often having several dependents. In addition, there are challenges for compliance with ILO conventions, due to intrinsic characteristics of informality itself.